Contesto e sequenze stratigrafiche della basilica padovana di Santa Giustina - Brogiolo, Gian Pietro (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
Despite a large number of studies on the church of Santa Giustina in Padua, we know little about the context in which it was founded, the date of its foundation, the plan and its development in the Middle Ages. With the aim of providing useful elements for these problems, the contribution discusses the sequence of the architectural remains preserved in elevations and the stratigraphy documented by three old excavations.